Analysis And Design Of Enterprise Architecture Using Togaf Adm In Analytic Of Customer Care Management At Telecommunication Company - Lanusgana Amerta; Yuli Prasetyo; Basuki Rahmad (eProceedings of Engineering, 2017)
PT XYZ is one of the biggest cellular telecommunication provider in Indonesia. One of its main concern is Customer Care Management. This research focuses on the Analytic of Customer Care Management, which positioned under Sales Directorate. Analytic of Customer Care Management has the main purpose to do analytical services and strategies, policies, and processes management for Customer Care Management. In this research, TOGAF is being used to develop Analytic of Customer Care Management’s enterprise architecture. This research is limited only from preliminary phase to migration planning phase. In each of these phase, existing architects are being identified and also target architectures are being proposed. Hopefully, this research could help provide insight to the telecommunication company regarding baseline of Analytic of Customer Care Management. Keywords: Enterprise Architecture, TOGAF ADM, Customer Care Management, Telecommunication Company